Osteoma Presenting as a Painless Solitary Mastoid Swelling - Hazem M. Abdel Tawab; Ravi Kumar V; Salim M. Sloma Tabook (Case Reports in Otolaryngology)
Introduction. Osteoma of the temporal bone is a very uncommon benign tumor of bone. Osteomas may occur in the external auditory canals but are reported to be very rare in the mastoid bone. Case Report. A 36-year-old male presented to our department with a hard swelling behind the right ear diagnosed as osteoma. Complete excision was done through a postauricular approach. Histopathology confirmed the diagnosis of osteoma. Conclusion. Osteomas, although rare, should be considered when dealing with any hard mastoid swelling. Complete removal can be ensured by drilling till the normal cortical bone is reached to avoid recurrence. A cortical mastoidectomy should be done if the mastoid air cell system is involved.